Law effectiveness criteria in consideration of unusual/atypical forms of employment - Brzostek, Krzysztof (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
An issue of the economic effectiveness of law is not often analysed. It can be caused by the elaborateness and multivocality of the term “effectiveness”. The incompatibility in the interpretation of the category of effectiveness can result from adopting different research perspectives. The lack of consensus on how to deal with the ambiguity of the term “effectiveness” creates a theoretical and cognitive gap that influences difficulties, including designing measurement systems. The research perspective of the economic analysis of law may be relevant to the consideration and analysis of atypical forms of employment carry out to determine the effectiveness of individual solutions.